2020
DOI: 10.1101/2020.05.11.20093732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assisting Scalable Diagnosis Automatically via CT Images in the Combat against COVID-19

Abstract: The pandemic of coronavirus Disease 2019 (COVID-19) caused enormous loss of life globally. 1-3 Case identification is critical. The reference method is using real-time reverse transcription PCR (rRT-PCR) assays, with limitations that may curb its prompt large-scale application. COVID-19 manifests with chest computed tomography (CT) abnormalities, some even before the onset of symptoms. We tested the hypothesis that application of deep learning (DL) to the 3D CT images could help identify COVID-19 infections. U… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…As far as performance is concerned, the system developed in [66] obtained 100% sensitivity. Among the reviewed systems, most of the frameworks [60] – [62] , [64] , [66] , [105] , [108] , [109] , and [111] achieved comparatively higher accuracy, sensitivity, specificity, precision, F1-score and AUC having these measure (where applicable) greater than 90%. The highest accuracy of 99.51% and 99.68% were found at [66] , [122] using pre-trained model and customized network respectively.…”
Section: Open Discussion Challenges and Future Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…As far as performance is concerned, the system developed in [66] obtained 100% sensitivity. Among the reviewed systems, most of the frameworks [60] – [62] , [64] , [66] , [105] , [108] , [109] , and [111] achieved comparatively higher accuracy, sensitivity, specificity, precision, F1-score and AUC having these measure (where applicable) greater than 90%. The highest accuracy of 99.51% and 99.68% were found at [66] , [122] using pre-trained model and customized network respectively.…”
Section: Open Discussion Challenges and Future Trendsmentioning
confidence: 99%
“…The experimental outcomes revealed that the scheme achieved accuracy, sensitivity, specificity, precision, and F1-score of 79.3%, 83%, 67%, 55%, and 63% respectively on the testing samples. Moreover, Liu et al [108] developed an automatic COVID-19 diagnosis system using deep learning method via CT images. The system used modified DenseNet-264 (COVIDNet) for diagnosis where the model consisted of 4 dense blocks.…”
Section: Custom Deep Learning Techniquesmentioning
confidence: 99%
“…(2020) proposed a uncertainty vertex-weighted hypergraph learning method for identifying COVID-19 from CAP with image features and radiometric features. Other classification work includes detection of COVID-19 from negative cases ( Jin, Wang, Xu, Luo, Wei, Zhao, Hou, Ma, Xu, Zheng, et al., 2020b , Jin, Chen, Cao, Xu, Zhang, Deng, Zheng, Zhou, Shi, Feng, 2020a , Liu, Liu, Dai, Yang, Xie, Tan, Du, Shan, Zhao, Zhong, Lin, Guan, Xing, Sun, Wang, Zhang, Fu, Fan, Li, Zhang, Li, Liu, Xu, Du, Zhao, Hu, Fan, Wang, Wu, Nie, Cheng, Ma, Li, Jia, Liu, Guo, Huang, Shen, An, Li, Zhou, He, 2020a ), image-level and patient-level detection of COVID-19 ( Chen et al., 2020a ), radiomics models for prediction of hospital stay (long term or short term) ( Qi et al., 2020 ).…”
Section: Related Workmentioning
confidence: 99%
“…Considering CT imagery, Wang et al [32] modify the inception concept [20] to present a smaller feature dimension. Accordingly, Liu et al [33] alter DenseNet-264 [34] to present four dense blocks. Custom deep learning models also utilize X-ray imagery.…”
Section: B Custom Modelsmentioning
confidence: 99%
“…Accordingly, Liu et al . [33] alter DenseNet-264 [34] to present four dense blocks. Custom deep learning models also utilize X-ray imagery.…”
Section: Literature Reviewmentioning
confidence: 99%